DINAMIKA PERGESERAN PILIHAN POLITIK PEMILIH DI KABUPATEN PATI DALAM PEMILU LEGISLATIF TAHUN 2009 DAN PEMILU LEGISLATIF TAHUN 2014 - Boneta Indriana; Purwoko .; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2016)
Indonesia has already implementing direct elections as many as four times since1999. Direct Election aims to choose the leaders of the country in accordancewith the will of the people through the system and the mechanism that has beendetermined. The political dynamics and non-state actors that participate in theelection on every few always changed. The changes occur is then affect the resultof votes at the General Election was held. As happened in the Pati District, theresult of the total votes for candidate for legislative election for members of theLocal Parliament of also experienced the movement since the Election 2004 untilthe election year 2014.The purpose of this research to know the image of a shift inthe attitudes of the mass political constituencies in the Pati District from theLegislative Election Year 2009 to the Legislative Election Year 2014, and to knowthe factors that cause a shift in the attitudes of the mass political constituencies inthe Pati District from the Legislative Election Year 2009 to the legislative electionyear 2014.The research method used in this writing qualitative research method.That is based on the primary data source the vote recapitulation data is thenanalyzed and supported by the secondary data which is derived from the interviewto voters in Pati district based on their experiences and knowledge.Based on the results of research can be known that in Pati is a shift in theattitudes of the mass political voter from one political party to the other politicalparties. A shift occurred from voice in the legislative year 2009 to the legislativeelection year 2014 almost happened in every sub-districts in Pati. The result ofthe existence of a shift in the sound affect the composition of the Legislativemembers of the DPRD Pati. While to know the factors that affect the changes inthe behavior of voters used the sociological approach, psychological, politicalrational, and dominant cognitive problems. Known factors that affect a shift in theattitudes of the mass political constituencies in the Pati district was divided intotwo factors namely common factors and special factors. Common factors consistof the influence of the mass media, Figure candidates and national leaders of theparty, the emergence of new parties, corruption cases that traps cadres ofpolitical party in the period of the reign of 2009-2014.Recommendations for further research, more deepen the cause of thephenomenon that is found in this research. In addition can also add various datasources e.g. from the point of view of the local political figures.Keywords : Voters, Voting Behavior, Pati District